2013
DOI: 10.1016/j.bios.2012.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Parallel recording of neurotransmitters release from chromaffin cells using a 10×10 CMOS IC potentiostat array with on-chip working electrodes

Abstract: Neurotransmitter release is modulated by many drugs and molecular manipulations. We present an active CMOS-based electrochemical biosensor array with high throughput capability (100 electrodes) for on-chip amperometric measurement of neurotransmitter release. The high-throughput of the biosensor array will accelerate the data collection needed to determine statistical significance of changes produced under varying conditions, from several weeks to a few hours. The biosensor is designed and fabricated using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 47 publications
1
81
0
2
Order By: Relevance
“…The tip of the carbon fiber was entirely coated with wax and then cut such that only the circular area at the end of the cut fiber was exposed as the working electrode. The area of such a CFM is similar to that of onchip electrodes after post-fabrication [11], [13], which also will be fabricated in the future on the FSCV chip described here. The CFM was immersed into a petri dish filled with a buffer solution containing 140 mM NaCl, 5 mM KCl, 5 mM CaCl 2 , 1 mM MgCl 2 , and 10 mM HEPES/NaOH pH 7.3.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tip of the carbon fiber was entirely coated with wax and then cut such that only the circular area at the end of the cut fiber was exposed as the working electrode. The area of such a CFM is similar to that of onchip electrodes after post-fabrication [11], [13], which also will be fabricated in the future on the FSCV chip described here. The CFM was immersed into a petri dish filled with a buffer solution containing 140 mM NaCl, 5 mM KCl, 5 mM CaCl 2 , 1 mM MgCl 2 , and 10 mM HEPES/NaOH pH 7.3.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The detector array provides a five-fold increase in temporal resolution over the unidirectional-current detector array we reported previously in [11], [13]. …”
Section: Introductionmentioning
confidence: 97%
“…To overcome this problem and incorporate more sensors into a chip-based device, semiconductor technology has been employed. [59][60][61][62][63][64][65][66][67][68] For instance, Lindau and colleagues reported the development of a complementary metal oxide semiconductor (CMOS)-based chip containing 10 © 10 microelectrodes for use in the detection of dopamine. 68 We developed an LSI-based amperometric sensor for electrochemical imaging, [69][70][71][72] designated the Bio-LSI system, first reported by Inoue et al 69 The Bio-LSI system is based on CMOS technology and provides higher temporal resolution for the detection of electrochemical species at different locations on the chip.…”
Section: Lsi-based Chip Devices For Bioanalysismentioning
confidence: 99%
“…7 Kim et al recently reported a complementary metal oxide semiconductor (CMOS)-based electrode array containing 100 electrodes for the simultaneous recording of exocytotic events from cells. 8 We previously developed a Bio-LSI (large-scale integration) device for the characterization of biomaterials that comprises 400 electrochemical sensors with a pitch of 250 µm arranged to form a LSI-based amperometric device. [9][10][11][12][13][14] The device is based on CMOS technology and an operational amplifier is incorporated into each sensor.…”
Section: Introductionmentioning
confidence: 99%